Knight's Microsoft SQL Server 2012 integration services 24-hour trainer - Knight, Brian 1976- (Wiley, 2013)
Book-and-video package gets novices up to speed on Microsoft SQL Server 2012 If you need a practical, hands-on introduction, especially to SQL Server Integration Services (SSIS), this book-and-video package from authority Brian Knight is the perfect solution. Each lesson includes three major components: a description of how each SSIS feature or process works, a tutorial that walks you through the process or technique, and an accompanying video lesson. It's a complete learning package that will give you the confidence you need to start your first SSIS project. Guides novice.
Includes bibliographical references and index. - Print version record
Keywords: SQL server; Database management; Bases de données; Gestion; COMPUTERS; Data Processing